1999
DOI: 10.1044/1059-0889(1999/001)
|View full text |Cite
|
Sign up to set email alerts
|

SP/AP Area Ratio in the Diagnosis of Ménière's Disease

Abstract: Conventional analysis of the click-evoked electrocochleogram includes measurement of the amplitudes of the cochlear summating potential (SP) and auditory nerve action potential (AP) to derive the SP/AP amplitude ratio. It is now well documented that an amplitude ratio where SP is elevated relative to AP may be a positive finding for endolymphatic hydrops in patients suspected of having Ménière's disease (MD). However, the incidence of an elevated SP/AP amplitude ratio in the general MD population is only appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 18 publications
5
52
1
3
Order By: Relevance
“…The SP and AP areas were also measured referring to previous studies [8]. An image of a wave form of AP and SP complex was captured by an image scanner (ES 2200, Epson, Japan).…”
Section: Measurement Of the Sp/ap Amplitude And Area Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…The SP and AP areas were also measured referring to previous studies [8]. An image of a wave form of AP and SP complex was captured by an image scanner (ES 2200, Epson, Japan).…”
Section: Measurement Of the Sp/ap Amplitude And Area Ratiomentioning
confidence: 99%
“…Therefore, a more sensitive diagnostic tool for MD and ELH has been anticipated. Recently, it was reported that the SP/AP area curve ratio in extratympanic ECochG significantly improved the diagnostic sensitivity of ELH in comparison with conventional SP/AP amplitude ratio in MD [8,9]. Ferraro and Tibbils [8] showed that the SP/AP area curve ratio was abnormally high in 44% of probable cases of MD (11/25) as well as in 90% of definite cases of MD (18/20).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…One might speculate that more-experienced surgeons will perform more precise, and involuntarily less traumatic, lesions. In our experiment, performed by the same surgeon with experience in this technique performed in a previous study 11 , we demonstrated that the sheep utricle is capable of withstanding surgical trauma without complete loss of cochlear function.…”
Section: Discussionmentioning
confidence: 82%
“…The analysis of the variable area was included in our study since it also represents a good parameter of interpretation of nerve conduction studies. The calculation of the SP/AP area ratio, described in some studies 11,12 and used in the present study, stands out as a very sensitive test to assess cochlear response to hearing stimulus in Ménière's disease, as well as in situations in which the cochlea is at risk due to surgical injury 13 . Since SP/AP area ratio is the integral of a function of the combination between amplitude and duration of action potential, Riemann integral reflects the number and synchronism of activated nerve fibers.…”
Section: Discussionmentioning
confidence: 99%